STUDENTS’ DIFFICULTIES IN ANSWERING THE LISTENING SECTION OF TOEFL ITP - Nora Nuraida; Sartika (STKIP Paracendekia NW Sumbawa, 2025)
The aim of this study was to identify the difficulties experienced by students in answering the listening section of the TOEFL ITP. This qualitative study involved students from the English and Mathematics Education Study Programs who had taken the TOEFL test at least twice but had not met the listening section standard score. Data collection techniques included documentation, questionnaires, and interviews. The results revealed external factors such as the speaker’s accent, speed, intonation, pauses, diction, complex sentence structures, and audio clarity. Internal factors included limited practice, memory and hearing limitations, low motivation, poor concentration, limited vocabulary, boredom, distractions, and difficulties in identifying key words. This study emphasizes the importance of addressing both internal and external challenges to improve student performance in the TOEFL listening section.